ChemInform Abstract: N, N‐Bond Formation in Intramolecular Cobalt‐Catalyzed [2 + 2 + 2] Cyclizations of Alkynyl‐Linked Bisnitriles, and the Preparation of Annulated Pyridazines. Issue 22 (3rd June 2014) - Snyder, John K.; Cai, Cuifang; Audet, Megan A.
Abstract Substitution at the propargyl position increases the steric hindrance and inhibits the reaction.